SOCIAL STATUS AND PROBLEMS OF FISHING COMMUNITY AT ALLAHABAD - PAYNE, A. L.; KATIHA, PRADEEP K.; SINGH, H. R.; SINGH, P. R.; PANDEY, S. K. (Journal of Indian Fisheries Association, 2015)
The paper highlights social status and sociomeconomic problems offishermen living along the Ganga and the Yamuna at Allahabad. Sincethe problems of fishermen varied with respect to category (with ownedboat and with hired boat) and location, significance of this variation wastested by x 2-test. The paper further emphasises on an intensive study offishermen community to have indepth analysis of their problems and tosuggest remedial measures for their upliftment.